Road network design with space syntax in Vendas Novas - Ourique, L. (2017)
The city of Vendas Novas, Évora, Portugal, is crossed by a national road. Currently, 30.000 to 35.000 vehicles cross the city, of which more than 2.000 are heavy motor vehicles. Due to the negative effects of the high levels of traffic, the city council as long proposed an alternative route to Estrada Nacional 4. To better understand the effects of an alternative route to the city of Vendas Novas our study applies an axial map analysis to the city current road network system and the two proposals currently being studied by the local city council and national infrastructure management entity. Based on this analysis a new proposal was drawn by our team to optimize the diversion of traffic from the city centre. Through the application of an axial map analysis, in this study our team hoped to demonstrate and disseminate near the local city management entities the potential and validity of this tool to the current and future planning of cities and, in particular, road networks.